Pozamelodyczne elementy improwizacji i ich rola w edukacji jazzowej = Non-melodic elements of jazz improvisation and their role in jazz education - Majewski, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is a personal reflection on ongoing shape of jazz education in Poland, as well as an attempt to draw attention to, according to the author, key elements of acquiring an artistic workshop that seem to be insufficiently discussed during the process of academic and earlier musical education.
Keywords: improvisations; jazz education; means of expression; artistic personality